Predictions of the results of laboratory tests on a clay using a critical state model. - Houlsby, G; Wroth, C; Wood, D (Balkema, 1984)
An elastic-plastic model for describing the stress-strain behaviour of a clay is presented. The model is based on the Modified Cam-Clay model, but includes an additional yield surface to model failure of overconsolidated samples on a Hvorslev surface. The model is used to predict the behaviour of a kaolinite in a number of repeated loading tests, based on the results of monotonic triaxial compresson and extension tests. -from Authors